Athletes' motivation, anxiety, and locus of control at the Brazilian powerchair football national championship - Angela Nogueira Neves; Marcelo Callegari Zanetti; Joelson Guilherme de Almeida; Míriam Raquel Meira Mainenti; Patrícia dos Santos Vigário (European Federation of Adapted Physical Activity, 2022)
The aim of this study was to evaluate motivation, competitive anxiety, locus of control and their associations with performance and training parameters. This cross-sectional study included 24 male athletes (Mage = 28.3 years, SD = 11.0) who were approached during the functional classification session, the day prior to the start of the Brazilian Powerchair Football National Championship and invited to participate in the study. The Sports Motivation Scale-II, Competitive State Anxiety Inventory-2, and Locus of Control in Sports Scale were used to collect data. From the results, autonomous motivation was more prominent than controlled motivation and amotivation. In addition, athletes were more self-confident than anxious and more frequently perceived internal and external locus of control than a "greater forces" locus. Internal locus of control was correlated with years of practice, hours of training, and sessions per week. Furthermore, cognitive and somatic anxiety were positively correlated with training sessions per week. Long-term follow-up of these athletes would allow better understanding how to promote and maintain a positive athletic psychological profile, ultimately affecting sports performance.